The emigration of Spanish scientists to Bochum: a difficult adaptation and an out-of-synchronized return - Rodríguez Puertas, Rubén (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper analyzes the speeches of Spanish scientists residing in Bochum (Germany), and of those who, after spending a long period in that city, had returned. It shows how they experience a difficult adaptation characterized by a feeling of job undervaluation, a lack of stability and the longing for certain aspects of Spanish culture such as the quality of leisure and the greater sociability of its population. On the other hand, a singular return is observed due to the desynchronization with their places of origin, because they feel that time has passed very quickly in them, while for them their lives have slowed down.